2009
DOI: 10.1093/humrep/dep345
|View full text |Cite
|
Sign up to set email alerts
|

Children raised in mother-headed families from infancy: a follow-up of children of lesbian and single heterosexual mothers, at early adulthood

Abstract: The findings of this study show that children raised by solo heterosexual mothers or lesbian mothers from infancy continue to function well as they enter adulthood. The findings are of relevance to the UK Human Fertilisation and Embryology (2008) Act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 24 publications
5
85
1
9
Order By: Relevance
“…Likewise, Gartrell and Bos (2010) found that these adolescents were functioning at least as well, and in some instances better, than expected from adolescent CBCL norms. Similar findings were obtained from the Fatherless Families Study in the United Kingdom when adolescents and young adult offspring parented by lesbian mothers were compared with those parented by heterosexual single mothers or heterosexual married couples (Golombok & Badger, 2010;, with young adults who had grown up in mother-headed families (either single heterosexual mothers or lesbian mothers) showing lower levels of anxiety, depression, hostility, and problematic alcohol use, coupled with higher levels of self-esteem, than did young adults from father-present families.…”
Section: Psychological Adjustment Of Adolescent and Young Adult Offspsupporting
confidence: 70%
See 3 more Smart Citations
“…Likewise, Gartrell and Bos (2010) found that these adolescents were functioning at least as well, and in some instances better, than expected from adolescent CBCL norms. Similar findings were obtained from the Fatherless Families Study in the United Kingdom when adolescents and young adult offspring parented by lesbian mothers were compared with those parented by heterosexual single mothers or heterosexual married couples (Golombok & Badger, 2010;, with young adults who had grown up in mother-headed families (either single heterosexual mothers or lesbian mothers) showing lower levels of anxiety, depression, hostility, and problematic alcohol use, coupled with higher levels of self-esteem, than did young adults from father-present families.…”
Section: Psychological Adjustment Of Adolescent and Young Adult Offspsupporting
confidence: 70%
“…The UK follow-up of children raised by lesbian mothers after their mothers and fathers had separated found that, in their mid-20s, offspring continued to report close relationships with their mothers and had closer stepparenting relationships with their mothers' female partners than adults in the heterosexual mother comparison group had with their mothers' male partners . In the Fatherless Families Study, a longitudinal study of planned lesbian families that included comparison groups of families headed by single heterosexual mothers and married heterosexual parents, the children were first interviewed at Age 3 to 9 years (Golombok, Tasker, & Murray, 1997), followed up at Age 12 ) and again at Age 18 (Golombok & Badger, 2010). Mother-child relationships were found to be closer in both types of fatherless families in childhood, and early adolescent children in fatherless families again reported closer relationships with their mothers, although mothers in fatherless families also reported more severe disputes with their adolescent offspring.…”
Section: Parentingmentioning
confidence: 99%
See 2 more Smart Citations
“…A long-term follow up of a small sample of single-parent families in the UK where the child had been raised since the fi rst year of life without a father, or father-fi gure, in a fi nancially stable family home, were found to be similar to traditional families in a range of measures assessing quality of parenting and child psychological adjustment at age six (Golombok et al 1997), twelve (MacCallum andGolombok 2004) and eighteen (Golombok and Badger 2010). In early adulthood those from solo mother households showed lower levels of anxiety, depression, hostility and problematic alcohol use than their counterparts from traditional families and the same levels as those raised in lesbian couple families, indicating that this family form may actually be 'better' for children than the nuclear family held as ideal.…”
Section: Single Motherhood By Choice: a Legitimate Family Formmentioning
confidence: 99%